2020
DOI: 10.21608/scuj.2020.119483
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mixing Rotational Speed on Characteristics of Edible Film Containing Tangerine (Citrus reticulate) Essential Oil to Extend the Shelf-Life of Mushroom (Agaricus bisporus)

Abstract: Mushrooms are products which lose their unique organoleptic properties after harvesting and, it has a short shelf life. The effect of edible coating of mushroom on shelf life was evaluated by using carrageenan (1.5%) and different concentrations of tangerine (Citrus reticulate) essential oil (0.2, 0.4 and 0.6%). Edible coating solutions were prepared using different rotational speed of mixing (500, 1000 and 1500 rpm). Physiochemical properties of tangerine essential oil and rheological characteristics of edibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…These viscous gums solutions have excellent barrier and adhesive capabilities, which can be used in the formation of edible coatings for the preservation of food products 61,76 It clarified that carrageenan-based edible coating prevented microbiological growth and lipid oxidation to preserved fresh fillets. In another study, Riyad et al 78 examined the impact of an edible coating made from 0.2%, 0.4%, 0.6% of tangerine peel essential oil (TPEO), and 1.5% of carrageenan on the shelf life of edible mushrooms. The results indicated that mushrooms can be preserved longer by coating them with a coating film consisting of carrageenan and TPEO.…”
Section: Gums-based Coatings Enriched With Eosmentioning
confidence: 99%
“…These viscous gums solutions have excellent barrier and adhesive capabilities, which can be used in the formation of edible coatings for the preservation of food products 61,76 It clarified that carrageenan-based edible coating prevented microbiological growth and lipid oxidation to preserved fresh fillets. In another study, Riyad et al 78 examined the impact of an edible coating made from 0.2%, 0.4%, 0.6% of tangerine peel essential oil (TPEO), and 1.5% of carrageenan on the shelf life of edible mushrooms. The results indicated that mushrooms can be preserved longer by coating them with a coating film consisting of carrageenan and TPEO.…”
Section: Gums-based Coatings Enriched With Eosmentioning
confidence: 99%